Pengaruh Gaya kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Mediasi (Studi Kasus Pada PT. Saktijaya Artha Pratama Makassar) - Hasbiyadi Hasibiyadi; Dennyson Evan Thenelsia; Muh. Syaiful Syahruddin; Putri Pertiwi (Universitas Muhammadiyah Tangerang, 2021)
Research This aims to determine: (1) the influence of leadership style variables on employee job satisfaction, (2) The influence of work environment variables on job satisfaction, (3) The influence of leadership style variables on employee performance, (4) The influence of work environment variables on employee performance, (5) The influence of job satisfaction variables on employee performance, (6) The influence of leadership style variables on employee performance through job satisfaction as a mediating variable, and (7) The influence of work environment on employee performance through job decision as a mediating variable at PT.Saktijaya Artha Pratama Makassar. The population in this study were employees of PT. Saktijaya Artha Pratama, totaling 45 employees. The sampling method in this study used the Nonprobability Sampling approach. The method of collecting observation data and questionnaires. The results of this study were that leadership style and work environment had a positive and significant effect directly on satisfaction. work, but don't yes leadership and work environment do not have a significant direct effect on employee performance and job satisfaction can mediate the influence of leadership style and work environment on employee performance at PT. Saktijaya Artha Pratama.Keywords: Leadership Style, Work Environment, Job Satisfaction, Employee Performance